2021
DOI: 10.1111/jvim.16095
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino acid concentrations during experimental hyperinsulinemia in 2 laminitis models

Abstract: Background: Endocrinopathic laminitis develops in association with insulin dysregulation, but the role of insulin in the pathogenesis remains unclear.Hyperinsulinemia can cause hypoaminoacidemia, which is associated with integumentary lesions in other species and therefore warrants investigation as a potential mechanism in laminitis.Objective: Evaluate plasma amino acid concentrations in the euglycemichyperinsulinemic clamp (EHC) and prolonged glucose infusion (PGI) laminitis models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 50 publications
(126 reference statements)
0
10
0
Order By: Relevance
“…These are not only influenced by the type of cancer, but also by the cancer stage [ 32 , 33 , 34 , 35 , 36 , 37 ]. The plasma amino acid profile seems to undergo specific changes during different diseases, not only in humans, but also in animals, which was previously shown in horses suffering from equine metabolic syndrome [ 38 , 39 ] or in experimentally-induced hyperinsulinemia [ 21 ].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These are not only influenced by the type of cancer, but also by the cancer stage [ 32 , 33 , 34 , 35 , 36 , 37 ]. The plasma amino acid profile seems to undergo specific changes during different diseases, not only in humans, but also in animals, which was previously shown in horses suffering from equine metabolic syndrome [ 38 , 39 ] or in experimentally-induced hyperinsulinemia [ 21 ].…”
Section: Introductionmentioning
confidence: 94%
“…Previous research has suggested that the increased endogenous glucocorticoid concentrations may be responsible for laminitis, since these are known to be associated with systemic insulin resistance [ 12 , 13 , 14 , 15 , 16 , 17 ]. The suspected mechanism is that binding of insulin to the insulin-like growth factor 1 receptor (IGF-1R) has an effect in the lamellar tissue of the hoof [ 18 , 19 , 20 ] and also that insulin can directly trigger laminitis even through mechanisms that have not yet been identified [ 21 ]. In addition to its effects on the glucose metabolism, insulin is an important regulator of protein metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The development of laminitis in horses is often associated with an endocrine disease (equine metabolic syndrome = EMS; pituitary pars intermedia dysfunction = PPID), in which insulin dysregulation occurs (EMS) or can occur (PPID) [ 1 , 2 , 3 ]. The suspected pathomechanism of endocrinopathic laminitis is hyperinsulinemia, but the mechanism by which hyperinsulinemia can cause laminitis remains unclear [ 4 ]. Based on the results of previous studies, it is suggested that insulin has an effect in the lamellar tissue of the hoof via the insulin-like growth factor 1 receptor (IGF-1R) [ 5 , 6 , 7 ], and also that insulin can directly trigger laminitis even through mechanisms that have not yet been identified [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The suspected pathomechanism of endocrinopathic laminitis is hyperinsulinemia, but the mechanism by which hyperinsulinemia can cause laminitis remains unclear [ 4 ]. Based on the results of previous studies, it is suggested that insulin has an effect in the lamellar tissue of the hoof via the insulin-like growth factor 1 receptor (IGF-1R) [ 5 , 6 , 7 ], and also that insulin can directly trigger laminitis even through mechanisms that have not yet been identified [ 4 ]. In addition to its effects on the glucose metabolism, insulin is an important regulator of protein metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation